Surface-hardened embossed double-sided antistatic release film as well as preparation method and application thereof
By setting a hardened embossed layer and an anti-static ionization layer on the polyethylene terephthalate film, the problems of poor temperature resistance and insufficient anti-static properties of the existing embossed release film are solved, and high Residual adhesion rate and low silicon migration effect are suitable for high-performance applications of industrial adhesive tapes.
Patent Information
- Application Number
- CN202411304699.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The existing embossed release films have problems such as poor temperature resistance, low residual adhesion rate, risk of silicon migration and insufficient antistatic performance, which is difficult to meet the high-performance needs of industrial adhesive tapes.
Using a surface-hardened embossed double-sided anti-static ionization film, the hardened embossed layer and anti-static ionization layer are provided on the polyethylene terephthalate film. The hardened embossed layer is modified from silicone-modified polyurethane acrylic acid. The anti-static ionization layer is composed of a conductive polymer resin, a platinum chelate catalyst, etc., and is prepared in combination with photocuring and thermal curing technologies to improve the temperature resistance and anti-static properties of the film.
It significantly improves the temperature resistance, residual adhesion and antistatic properties of the embossed release film, reduces the risk of silicon migration, enhances the weather resistance and peeling force of the film, and is suitable for the production of high-demand industrial adhesive tapes.
Smart Images

Figure CN119192646A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of embossed release films, and in particular relates to a surface-hardened embossed double-sided antistatic release film and a preparation method and application thereof. Background Art
[0002] In recent years, due to the rapid iteration and update of technology, many electronic products have been pursuing thinning and lightweight, which has led to the continuous development of industrial functional adhesive tapes used in this field in the direction of thinning and lightweight, thus putting forward higher requirements on the performance of adhesive tapes. The performance of the adhesive layer with a thickness of 30μm in the past now needs to be achieved at a thickness of 10μm, especially the performance in terms of high adhesion and long-term weather resistance.
[0003] Thinning brings good user experience, but it also brings great challenges to the manufacturing process of industrial functional adhesive tapes. On the one hand, the substrate is constantly thinning, and the thinning of the adhesive layer leads to deformation in the manufacturing process and deformation during application in later use. At present, in order to solve the needs of application deformation and bubble removal, embossed release film products have been developed, which can effectively solve the problem of bubbling in the process of large-area application. For example, car color change film is a type of embossed release film product.
[0004] In the past, since polyester (PET) film is produced by a biaxial stretching process, it is impossible to produce an embossed effect in the film making process. In addition, these embossed films account for a relatively low proportion of the PET film. Therefore, this type of embossed film is mostly produced by a laminating process (i.e., a layer of polyethylene is applied to the PET film or paper by a laminating machine, and then the polyethylene is molten and pressed together through a mold cooling wheel with lines). Some are produced by a hot pressing mold in the later stage, but the latter method cannot achieve a good effect due to the poor lateral uniformity of the embossing. Therefore, the current mainstream production method is to coat a layer of polyethylene (PE) film on the PET substrate, and then produce embossing through an embossed mold (embossing wheel) during the laminating process. This method solves the unevenness of the lateral depth, but due to the low temperature resistance of PE, it limits the curing conditions of the silicone used in the release film coating, and also limits the conditions for the application of downstream adhesive tapes.
[0005] In summary, the current embossed release films have the disadvantages of poor temperature resistance, low residual adhesion rate, risk of silicon migration and low antistatic performance. Summary of the invention
[0006] The purpose of the present invention is to provide a surface-hardened embossed double-sided antistatic release film and a preparation method and application thereof. The surface-hardened embossed double-sided antistatic release film provided by the present invention has excellent temperature resistance, high residual adhesion rate and low silicon migration. At the same time, the depth change rate of the grain line is small and it has double-sided antistatic function, so that high peeling force and long-term weather resistance can be obtained, which significantly improves the product quality of the embossed release film.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a surface hardened embossed double-sided antistatic release film, comprising a polyethylene terephthalate (PET) film, a hardened embossed layer arranged on the front side of the polyethylene terephthalate film, an antistatic release layer arranged on the surface of the hardened embossed layer, and an antistatic layer arranged on the back side of the polyethylene terephthalate film;
[0009] The hardened embossed layer is obtained by photocuring a surface hardening coating, wherein the surface hardening coating comprises a siloxane-modified polyurethane acrylic monomer, an acrylate monomer, a first organic solvent, a flattening agent and a photoinitiator;
[0010] The antistatic release layer is formed of an antistatic release coating, and the antistatic release coating includes a conductive polymer resin, an anchoring agent, an organic polysiloxane, a polyhydrogen siloxane, a platinum chelate catalyst, and a second organic solvent.
[0011] Preferably, the acrylate monomer is trimethylolpropane triacrylate, and the first organic solvent is toluene;
[0012] The mass ratio of the siloxane-modified polyurethane acrylic monomer to the acrylate monomer is (35-40): (20-25);
[0013] The mass ratio of the siloxane-modified polyurethane acrylic monomer to the leveling agent is (35-40): (3-5);
[0014] The mass ratio of the siloxane-modified polyurethane acrylic monomer to the photoinitiator is (35-40):3;
[0015] The viscosity of the surface hardening coating is 100-400 mPa·s.
[0016] Preferably, the surface hardening coating further comprises nano-silicon dioxide; the particle size of the nano-silicon dioxide is ≤30 nm; and the mass ratio of the siloxane-modified polyurethane acrylic monomer to the nano-silicon dioxide is (35-40):(3-5).
[0017] Preferably, the embossing depth of the hardened embossed layer is 10-30 μm, and the width of the embossing line interval is 0.5-2 mm.
[0018] Preferably, the conductive polymer resin comprises one or more of polythiophene, polythiophene derivatives and polyanionic polymers, the polyanionic polymer comprises polymeric hydroxy acid and / or polymeric sulfonic acid; the polymeric hydroxy acid comprises one or more of polyacrylic acid, polymethacrylic acid and polymaleic acid, and the polymeric sulfonic acid comprises polystyrene sulfonic acid;
[0019] The second organic solvent is n-hexane.
[0020] Preferably, the conductive polymer resin is polythiophene and / or a polythiophene derivative, and the mass ratio of the organopolysiloxane to the polythiophene and / or the polythiophene derivative is 100:(0.05-0.5);
[0021] The mass ratio of the organopolysiloxane to the anchoring agent is 100:(0.5-1);
[0022] The mass ratio of the organopolysiloxane to the polyhydrogensiloxane is 100:(1.5-3);
[0023] The mass concentration of the platinum chelate catalyst in the antistatic release coating is 50 to 80 ppm;
[0024] The solid content of the antistatic release coating is 1.5-5%;
[0025] The viscosity of the antistatic release coating is 10-40 mPa·s.
[0026] Preferably, the antistatic layer is formed by an antistatic coating, the antistatic coating includes an antistatic substance and a third solvent, the antistatic substance is polythiophene and / or a polythiophene derivative, the mass percentage of the antistatic substance in the antistatic coating is 0.05-0.5%, and the third solvent is water or isopropanol, or a mixture of water and isopropanol.
[0027] The present invention provides a method for preparing the surface-hardened embossed double-sided antistatic release film described in the above technical solution, comprising the following steps:
[0028] Using an embossing roller to apply a surface hardening coating on the front side of the polyethylene terephthalate film to obtain a surface hardened wet film, and then sequentially pre-drying and light-curing the surface hardened wet film to obtain a hardened embossed layer to obtain a first semi-finished product;
[0029] Using an anilox roller to apply an antistatic release coating on the surface of the hardened embossed layer of the first semi-finished product to obtain an antistatic release wet film, and then subjecting the antistatic release wet film to thermal curing to obtain an antistatic release layer to obtain a second semi-finished product;
[0030] The back side of the polyethylene terephthalate film of the second semi-finished product is coated with an antistatic coating to obtain an antistatic wet film, and then the antistatic wet film is dried to obtain the antistatic layer, thereby obtaining the surface-hardened embossed double-sided antistatic release film.
[0031] Preferably, the embossing depth of the embossing roller is 0.01-0.03 mm, the width of the embossing line interval is 0.5-2 mm, the humidity of the coating environment is ≤50%, the temperature is 25±5°C, the moving speed of the polyethylene terephthalate film is 50-100 m / min, the temperature of the surface hardening coating is 50-60°C, the pre-drying temperature is 110-130°C, the light curing is carried out under the condition of ultraviolet light irradiation, the wavelength of the ultraviolet light is 200-400 nm, and the dose of the ultraviolet light is 600-800 mj / cm 2 , power is 100~160W / cm;
[0032] The mesh number of the anilox roller is 80 to 200 meshes, and the coating wet weight of the antistatic release coating is 4 to 10 g / m 2 , the thermal curing temperature is 130-160°C, and the time is 8-10s;
[0033] The antistatic coating is coated by two gravure rollers, the mesh number of the gravure of the two gravure rollers is 300-350 meshes, and the coating wet weight of the antistatic coating is 3-5 g / m 2 .
[0034] The present invention provides the application of the surface-hardened embossed double-sided antistatic release film described in the above technical scheme or the surface-hardened embossed double-sided antistatic release film prepared by the preparation method described in the above technical scheme in semiconductors, automobile color-changing films, electronics, displays or touch screens.
[0035] The present invention provides a surface-hardened embossed double-sided antistatic release film, comprising a polyethylene terephthalate (PET) film, a hardened embossed layer arranged on the front side of the polyethylene terephthalate film, an antistatic release layer arranged on the surface of the hardened embossed layer, and an antistatic layer arranged on the back side of the polyethylene terephthalate film; the hardened embossed layer is obtained by photocuring a surface-hardening coating, the surface-hardening coating comprises a siloxane-modified polyurethane acrylic monomer, an acrylate monomer, a first organic solvent, a flattening agent and a photoinitiator; the antistatic release layer is formed by an antistatic release coating, the antistatic release coating comprises a conductive polymer resin, an anchoring agent, an organic polysiloxane, a polyhydrogensiloxane, a platinum chelate catalyst and a second organic solvent. On the one hand, the present invention adopts a hardened embossed layer to replace the PE coating in the prior art, and by reasonably optimizing the raw material type and film-forming method of the hardened embossed layer, the temperature resistance of the embossed release film product is significantly improved, and the obtained embossed release film has the advantages of high residual adhesion rate, low silicon migration, and small depth change rate of the grain line (≤10μm); on the other hand, the present invention arranges an antistatic release layer on the surface of the hardened embossed layer, and arranges an antistatic layer on the back of the polyethylene terephthalate film, and by optimizing the raw material type of the antistatic release layer, the excellent antistatic function of both sides of the embossed release film is achieved. In summary, the surface hardened embossed double-sided antistatic release film provided by the present invention can significantly reduce the amount of catalyst used in the production process of industrial adhesive tapes, improve the peeling force and weather resistance of industrial adhesive tapes, and at the same time has a good effect on electrostatic pollution and fine dust pollution caused by static electricity.
[0036] The results of the examples show that the surface hardening embossed double-sided antistatic release film provided by the present invention has a surface hardness of ≥2H (H is pencil hardness) and a temperature resistance of ≥150°C / 5min. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is an enlarged view of the structure of the embossed double-sided antistatic release film with a hardened coating provided by the present invention;
[0038] Figure 2 A schematic structural diagram of an embossed double-sided antistatic release film with a hardened coating provided by the present invention;
[0039] Figure 3 A flow chart of the preparation of the embossed double-sided antistatic release film with a hardened coating provided by the present invention. DETAILED DESCRIPTION
[0040] The present invention provides a surface hardened embossed double-sided antistatic release film, comprising a polyethylene terephthalate film, a hardened embossed layer arranged on the front side of the polyethylene terephthalate film, an antistatic release layer arranged on the surface of the hardened embossed layer, and an antistatic layer arranged on the back side of the polyethylene terephthalate film;
[0041] The hardened embossed layer is obtained by photocuring a surface hardening coating, wherein the surface hardening coating comprises a siloxane-modified polyurethane acrylic monomer, an acrylate monomer, a first organic solvent, a flattening agent and a photoinitiator;
[0042] The antistatic release layer is formed by an antistatic release coating, which includes a conductive polymer resin, an anchoring agent, an organic polysiloxane, a polyhydrogen siloxane, a platinum chelate catalyst and a second organic solvent; and the molecular structure of the organic polysiloxane contains a vinyl group.
[0043] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art. In the present invention, the viscosity of the following coatings is measured using a rotational viscometer.
[0044] The surface hardened embossed double-sided antistatic release film provided by the present invention comprises a polyethylene terephthalate film. In the present invention, the polyethylene terephthalate film is preferably optical grade. In the present invention, the polyethylene terephthalate film is preferably a double corona film, and the surface energy is preferably ≥54 dahns, preferably 54 to 56 dahns.
[0045] In a specific embodiment of the present invention, the polyethylene terephthalate film is preferably a Lucky Film. The size of the polyethylene terephthalate film is 50 μm×1040 mm, and the product model is FP613.
[0046] The surface-hardened embossed double-sided antistatic release film provided by the present invention comprises a hardened embossed layer arranged on the front side of the polyethylene terephthalate film. In the present invention, the hardened embossed layer is obtained by photocuring a surface-hardening coating, and the surface-hardening coating comprises a siloxane-modified polyurethane acrylic monomer, an acrylate monomer, a first organic solvent, a flattening agent, and a photoinitiator. In the present invention, the siloxane-modified polyurethane acrylic monomer is a modified polyurethane acrylic monomer containing siloxane, and its modified grafted group is siloxane.
[0047] In the present invention, the siloxane-modified polyurethane acrylic monomer is an organic silane-modified acrylic polyurethane UV-curable prepolymer.
[0048] In the present invention, the preparation method of the siloxane-modified polyurethane acrylic monomer comprises the following steps:
[0049] (1) adding isocyanate and catalyst in a weight ratio of 50 to 150:1 into a reactor, stirring, and then adding hydroxyethyl acrylate, reacting at 50 to 70° C. for more than 12 hours to obtain an acrylated polyurethane oligomer; wherein the weight ratio of the added hydroxyethyl acrylate to the isocyanate is 0.8 to 1.2:1;
[0050] (2) adding isocyanate and catalyst in a weight ratio of 30 to 70:1 into a reactor, stirring, adding organosilane, controlling the reaction temperature at 50 to 70° C., reacting for more than 24 hours, adding hydroxyethyl acrylate, reacting at 50 to 70° C. for more than 4 hours, and obtaining an organosilane-modified acrylic polyurethane oligomer; wherein the weight ratio of the added organosilane, hydroxyethyl acrylate and isocyanate is 3:1 to 2:3 to 9;
[0051] (3) mixing the acrylated polyurethane oligomer obtained in step (1) and the organosilane-modified acrylated polyurethane oligomer obtained in step (2), adding 0.01 to 2.0 wt % of an antioxidant, and stirring the mixture at 50 to 70° C. for more than 4 hours to obtain an organosilane-modified acrylated polyurethane UV-curable prepolymer; the acrylated polyurethane oligomer accounts for 5 to 95 wt % of the organosilane-modified acrylated polyurethane UV-curable prepolymer;
[0052] The catalyst is selected from the following one or any combination of two or more: stannous octoate, dibutyltin dilaurate, dibutyltin maleate, dibutyltin monobutyl maleate, triethylenediamine, N,N-dimethylbenzylamine. The isocyanate is a diisocyanate or a polyisocyanate, specifically 3-isocyanato methylene-3,5,5-trimethylcyclohexyl isocyanate. The organosilane is aminoorganosilane or mercaptoorganosilane or any combination thereof; the aminoorganosilane is 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, bis[(3-trimethoxysilyl)-propyl]amine, bis[(3-triethoxysilyl)-propyl]amine, one or any combination of two or more thereof; the mercaptoorganosilane is 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-thiocyanatepropyltriethoxysilane, one or any combination of two or more thereof. The organosilane is specifically 3-aminopropyltrimethoxysilane. The antioxidant is selected from the following one or any combination of two or more: 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, tris[2,4-di-tert-butylphenyl] phosphite, and the amount of the antioxidant is 0.05-1.5wt%.
[0053] In the present invention, the siloxane-modified polyurethane acrylic monomer is preferably obtained by referring to the preparation method disclosed in paragraphs 15 to 27 of the specification of the Chinese patent application publication number CN101864166A and the invention name "Preparation method of organic silane-modified acrylic polyurethane UV-curable prepolymer".
[0054] In a specific embodiment of the present invention, the siloxane-modified polyurethane acrylic monomer is obtained according to the preparation method of Example 1 in the Chinese patent application publication number CN101864166A and the invention name "Preparation method of organic silane-modified acrylic polyurethane UV-curable prepolymer".
[0055] In the present invention, the acrylate monomer is trimethylolpropane triacrylate. The first organic solvent is preferably toluene. The leveling agent is preferably silicone polyether leveling agent 401LS (Dow Corning Chemical Co., Ltd.). The photoinitiator is preferably 184D (1-hydroxycyclohexyl phenyl ketone, Xianyi Chemical).
[0056] In the present invention, the viscosity of the surface hardening coating is 100-400 mPa·s. The mass ratio of the siloxane-modified polyurethane acrylic monomer to the acrylate monomer is preferably (35-40): (20-25). The mass ratio of the siloxane-modified polyurethane acrylic monomer to the leveling agent is preferably (35-40): (3-5). The mass ratio of the siloxane-modified polyurethane acrylic monomer to the photoinitiator is preferably (35-40): 3.
[0057] In the present invention, the main function of the trimethylolpropane triacrylate is to adjust the viscosity and participate in the polymerization reaction. The trimethylolpropane triacrylate is beneficial to improving the flexibility and adhesion of the adhesive layer, and can also act as a cross-linking agent, which has an important influence on the hardness, toughness and strength of the hardened embossed layer.
[0058] In the present invention, the surface hardening coating preferably further comprises nano-silicon dioxide; the particle size of the nano-silicon dioxide is preferably ≤30 nm, more preferably 20 to 30 nm. The mass ratio of the organosiloxane-modified polyurethane acrylic monomer to the nano-silicon dioxide is preferably (35 to 40): (3 to 5).
[0059] As one or more embodiments of the present invention, the surface hardening coating preferably includes siloxane-modified polyurethane acrylic monomer, acrylate monomer, nano-silica, a smoothing agent, a photoinitiator and a first organic solvent. The mass ratio of the siloxane-modified polyurethane acrylic monomer, acrylate monomer, nano-silica, a smoothing agent, a photoinitiator and the first organic solvent is preferably 40:20:5:5:3:30 or 40:20:3:3:3:30.
[0060] In the present invention, the embossing depth of the hardened embossed layer (usually referred to as embossing depth, which is actually the height of the protruding lines) is preferably 10 to 30 μm, and the width of the interval between the lines is preferably 0.5 to 2 mm.
[0061] The surface hardened embossed double-sided antistatic release film provided by the present invention includes an antistatic release layer arranged on the surface of the hardened embossed layer. In the present invention, the antistatic release layer is formed by an antistatic release coating, and the antistatic release coating includes a conductive polymer resin, an anchoring agent, an organic polysiloxane, a polyhydrogen siloxane, a platinum chelate catalyst and a second organic solvent. In the present invention, the conductive polymer resin preferably includes one or more of polythiophene, polythiophene derivatives and polyanionic polymers, more preferably polythiophene and / or polythiophene derivatives, and the polythiophene derivatives preferably include poly-3-hexylthiophene, poly-3,4-ethylenedioxythiophene and poly-2,5-dibromo-3-(2-(4-2 hexyl-hexyloxy)-phenyl)-vinyl)-thiophene. One or more. The polyanionic polymer preferably includes polymeric hydroxy acid and / or polymeric sulfonic acid; the polymeric hydroxy acid preferably includes one or more of polyacrylic acid, polymethacrylic acid and polymaleic acid, and the polymeric sulfonic acid preferably includes polystyrene sulfonic acid.
[0062] In one or more embodiments of the present invention, the conductive polymer resin is preferably polythiophene, and more preferably poly(3,4-ethylenedioxythiophene).
[0063] In the present invention, the anchoring agent is preferably a silane coupling agent chelate. The anchoring agent is preferably one or more of Dow Corning 297, Chongyao 5176, Yongzhuo 295 and Jieguo 823. The anchoring agent can increase the adhesion of the antistatic release layer and the hardened embossed layer. The platinum chelate catalyst preferably includes one or more of Bluestar 92B, Dow Corning 5000, Wacker V24, Wacker V20 and Wacker V99. The second organic solvent is preferably n-hexane.
[0064] In the present invention, the organopolysiloxane is the main material of the antistatic release coating, and the polyhydrogensiloxane is the bridging agent of the antistatic release coating. In one or more specific embodiments of the present invention, the polyhydrogensiloxane is Bluestar 96A.
[0065] In the present invention, the conductive polymer resin is polythiophene and / or a polythiophene derivative, and the mass ratio of the organopolysiloxane to the conductive polymer resin is preferably 100:(0.05-0.5), more preferably 100:0.06, 100:0.1 or 100:0.5. The mass ratio of the organopolysiloxane to the anchoring agent is preferably 100:(0.5-1). The mass ratio of the organopolysiloxane to the polyhydrogensiloxane is preferably 100:(1.5-3), preferably 100:(2-3), more preferably 100:2.4. The mass concentration of the platinum chelate catalyst in the antistatic release coating is preferably 50-80 ppm. The solid content of the antistatic release coating is preferably 1.5-5%, specifically preferably 4%. The viscosity of the antistatic release coating should be 10-40 mPa·s.
[0066] In the present invention, the content of the conductive polymer in the antistatic release coating cannot be too high, because too high a content of the conductive polymer will affect the catalytic action of the platinum chelate catalyst and cause poor release curing, and may easily result in low residual adhesion and even easy rubbing off of the release layer.
[0067] In the present invention, the performance of the antistatic release layer satisfies: Z≤10E10; SAS≥80%; release force satisfies 0.04-1N / 25mm; temperature resistance is 150℃ / 5min, wherein: Z represents surface impedance, the unit is Ω, SAS is the residual adhesion rate (also called residual adhesion rate) is a dimensionless unit %.
[0068] The surface-hardened embossed double-sided antistatic release film provided by the present invention comprises an antistatic layer arranged on the back side of the polyethylene terephthalate film.
[0069] In the present invention, the antistatic layer is formed by an antistatic coating, and the antistatic coating includes an antistatic substance and a third solvent. The antistatic substance is preferably polythiophene and / or its derivatives, and the polythiophene derivatives preferably include one or more of poly-3-hexylthiophene, poly-3,4-ethylenedioxythiophene and poly-2,5-dibromo-3-(2-(4-2 hexyl-hexyloxy)-phenyl)-vinyl)-thiophene. In a specific embodiment of the present invention, the antistatic substance in the antistatic layer is poly(3,4-ethylenedioxythiophene). The mass percentage of the antistatic substance in the antistatic coating is preferably 0.05 to 0.5%. The third solvent is preferably water or isopropanol, or a mixture of water and isopropanol. The mass ratio of water and isopropanol in the mixture of water and isopropanol depends on the drying speed of the oven and the film surface effect, such as the effect of eliminating dark shadows. The water is preferably deionized water. The third solvent is preferably isopropanol or preferably a mixture of water and isopropanol, and the mass ratio of water and isopropanol is preferably 1:3.
[0070] In the present invention, the higher the isopropyl alcohol content in the mixture of isopropyl alcohol and water, the faster the drying speed will be. In addition, the appropriate isopropyl alcohol content can effectively obtain a clearer appearance and reduce the generation of spotty images.
[0071] In the present invention, the mass percentage of the antistatic substance in the antistatic coating is preferably 0.05-0.5%, and the higher the concentration, the lower the surface impedance.
[0072] In the present invention, the performance of the antistatic layer satisfies: Z≤10E10(10 10 ), where: Z represents the surface impedance in Ω.
[0073] The surface hardening embossed double-sided antistatic release film provided by the invention has a surface impedance of ≤10E10Ω, a release force of 0.04-10N, and a residual adhesion rate of ≥85%.
[0074] In summary, the surface hardened embossed double-sided antistatic release film provided by the present invention uses a hardened coating instead of a PE coating, and the obtained embossed double-sided antistatic release film has much better temperature resistance, line accuracy, lower line depth (can reach ≤10μm) and residual adhesion rate than the existing PE embossed release film. And the double-sided antistatic function is more suitable for high-requirement processes.
[0075] The present invention provides a method for preparing the surface-hardened embossed double-sided antistatic release film described in the above technical solution, comprising the following steps:
[0076] Using an embossing roller to apply a surface hardening coating on the front side of the polyethylene terephthalate film to obtain a surface hardened wet film, and then sequentially pre-drying and light-curing the surface hardened wet film to obtain a hardened embossed layer to obtain a first semi-finished product;
[0077] Using an anilox roller to apply an antistatic release coating on the surface of the hardened embossed layer of the first semi-finished product to obtain an antistatic release wet film, and then subjecting the antistatic release wet film to thermal curing to obtain an antistatic release layer to obtain a second semi-finished product;
[0078] The back side of the polyethylene terephthalate film of the second semi-finished product is coated with an antistatic coating to obtain an antistatic wet film, and then the antistatic wet film is dried to obtain the antistatic layer, thereby obtaining the surface-hardened embossed double-sided antistatic release film.
[0079] In the present invention, in the coating process described below, the coating speed is preferably 50 to 100 m / min.
[0080] The present invention uses an embossing roller to apply a surface hardening coating on the front side of the polyethylene terephthalate film to obtain a surface hardening wet film, and then the surface hardening wet film is sequentially pre-dried and photocured to obtain a hardened embossed layer to obtain a first semi-finished product. In the present invention, the hardened embossed layer is preferably prepared in a coating device. In the present invention, the polyethylene terephthalate film is preferably first placed on a reeling device of a coating device, and the cloth is threaded according to the threading requirements of the coating device. In the present invention, before applying the surface hardening coating, the present invention preferably performs a corona treatment and a pre-drying treatment on the front side of the polyethylene terephthalate film. The present invention preferably performs a corona treatment to ensure that its surface is 54 to 56 dahns. In the present invention, the preparation method of the surface hardening coating preferably includes the following steps: pre-mixing the siloxane-modified polyurethane acrylic monomer, the acrylate monomer and the first organic solvent to obtain a mixed solution; mixing the mixed solution, the leveling agent and the photoinitiator. The pre-mixing is preferably carried out under stirring conditions, and the pre-mixing time is preferably 30 minutes. The premixing is preferably carried out under ultrasonic stirring. The ultrasonic stirring used in the present invention has a good dispersing effect. The mixing of the mixed solution, the flattening agent and the photoinitiator is preferably carried out under stirring, and the stirring and mixing time is preferably 10 minutes.
[0081] In the present invention, before applying the surface hardening coating, the present invention preferably installs an embossed (concave) roller to a two-roll coating device, the embossed concave depth of the embossed roller is preferably 0.01-0.03 mm, and the width of the line spacing is preferably 0.5-2 mm. If the embossed concave depth of the embossed roller is too deep, the lines will be deformed or easily brittle and broken after coating, affecting the appearance and being unfavorable for the exhaust effect of the downstream products. In addition, in order to coordinate the transparency and coating thickness of the film after coating, the viscosity of the surface hardening coating is 100-400 mPa·s. The present invention preferably places the surface hardening coating in a bath of the coating device. The temperature of the surface hardening coating is preferably 50-60°C. The humidity of the environment during the coating is preferably ≤50%, the temperature is preferably 25±5°C, the temperature of the pre-drying is preferably 130-160°C, and the photocuring is carried out under the condition of ultraviolet light irradiation. In a specific embodiment of the present invention, the photocuring is preferably carried out under the condition of UV lamp irradiation. The wavelength of the ultraviolet light is preferably 200-400 nm, and the dosage of the ultraviolet light is preferably 600-800 mj / cm 2 The power is preferably 160 W / cm. During the coating of the surface hardening coating, pre-drying and light curing: the coating speed of the polyethylene terephthalate film is preferably 50-100 m / min.
[0082] After obtaining the first semi-finished product, the present invention uses an anilox roller to apply an antistatic release coating on the surface of the hardened embossed layer of the first semi-finished product to obtain an antistatic release wet film, and then heat cures the antistatic release wet film to obtain an antistatic release layer to obtain a second semi-finished product. In the present invention, before the coating, the present invention preferably performs a corona treatment on the surface of the hardened embossed layer of the first semi-finished product.
[0083] In the present invention, before the coating, the present invention preferably installs the anilox roller on a two-roller release coating device. The mesh number of the anilox roller is preferably 80-250 mesh, more preferably 80-200 mesh or 100-250 mesh. The anilox roller is preferably electro-engraved, and the anilox roller is preferably a ceramic roller made of a surface aluminum oxide coating to reduce the impact of the roller surface roughness on the appearance of the film, which is mainly reflected in the scratching of the film. In a specific embodiment of the present invention, the total runout of the anilox roller is ≤0.02mm; the total roundness is 0.014mm, and the dynamic balance is G6.3 / 300rpm. The present invention preferably places the antistatic release coating in the bath of the coating device. In the present invention, the coating wet weight of the antistatic release coating is preferably 4-10g / m 2 The temperature of the thermal curing is preferably 130-160°C, and the time is preferably 8-10s. The present invention preferably sets the temperature of the thermal curing to 130-160°C according to the coating speed and the total irradiation power. During the coating of the antistatic release coating and thermal curing: the moving speed of the first semi-finished product is preferably 50-100m / min.
[0084] In the present invention, the hardened embossed layer and the antistatic release layer are preferably completed in a dual-function coating device, and the dual-function coating device preferably includes two processes of UV curing and drying curing. The antistatic layer is preferably completed in another coating device.
[0085] In the present invention, the temperature of the heat curing oven is set to 130-160°C according to the coating speed and the total irradiation power. The temperature is distributed in the above curve, with the high value being in the middle of the oven. The coating speed is determined by the UV light dose and the length of the heat curing oven. However, because the two processes are connected in series, the speeds of the two processes must be coordinated. The correct situation is that the appearance of the film is not affected by the excessively high temperature of the oven (or the residence time is too long). These appearances are mainly caused by the deformation caused by the stretching of the film. In the heat curing process, under the same temperature conditions, The amount of platinum added to the antistatic release coating is also an important factor affecting the speed. When the platinum concentration of the coating solution is 50-80ppm, the thermal curing temperature is 160°C at the highest point, and the thermal curing residence time is 8-10s. And because platinum (in the form of chelates) is easily contaminated by nitrogen, phosphorus, tin, sulfur compounds and their ions, these substances must be excluded from the entire coating process. Otherwise, the residual adhesion rate will be reduced at the least, and the antistatic release layer will be rubbed off and the process will fail in severe cases.
[0086] After obtaining the antistatic release layer, the present invention directly obtains the initial second semi-finished product. After obtaining the initial second semi-finished product, the present invention preferably cools the initial second semi-finished product and then irons it to obtain the second semi-finished product. During the cooling, the water temperature of the cooling wheel is ≤35°C when the initial second semi-finished product is rolled up. If necessary, ice water is passed through the cooling wheel, and the ironed and cooled film is rolled up to be coated with an antistatic agent on the back.
[0087] After obtaining the second semi-finished product, the present invention applies an antistatic coating to the back of the polyethylene terephthalate film of the second semi-finished product to obtain an antistatic wet film, and then dries the antistatic wet film to obtain the antistatic layer, and obtains the surface hardened embossed double-sided antistatic release film. In the present invention, in the present invention, before the coating, the present invention preferably performs a corona treatment on the back of the second semi-finished product (i.e., the back of the polyethylene terephthalate film). The present invention preferably uses corona treatment to ensure that the back of the polyethylene terephthalate film is 54 to 56 dahns. The antistatic coating is coated with a gravure two-roller, and the mesh number of the gravure of the gravure two-roller is preferably 300 to 350 meshes, and the gravure two-roller is preferably an electric engraving method. The gravure two-roller is preferably a ceramic roller made of a surface aluminum oxide coating to reduce the impact of the roller surface roughness on the appearance of the film, and these impacts are mainly reflected in scratching the film. In a specific embodiment of the present invention, the total runout of the two gravure rollers is ≤0.02 mm; the total roundness is 0.014 mm, and the dynamic balance is G6.3 / 300 rpm. The coating wet weight of the antistatic coating is preferably 3 to 5 g / m 2. In the present invention, if the number of the gravure of the gravure two-roller is too small (the coating will become thicker), it will affect the coating appearance of the coated product, and it will easily produce light interference phenomenon. These light interference phenomena are mainly caused by the low viscosity of the liquid, which causes poor film (implantation) of the coating or uneven thickness of the coating. Therefore, a thin coating will have a positive effect on these defects. Of course, the appropriate method of adjusting the viscosity of the coating can also be well improved. In terms of solvent, the proportion of isopropanol can be increased. In the present invention, the drying temperature is preferably 10 to 20°C higher than the boiling point of the third solvent. When the third solvent is preferably water, the drying temperature is preferably 110 to 120°C. When the third solvent is preferably isopropanol or a mixture of water and isopropanol, the drying temperature is preferably 90 to 110°C. During the back coating of the antistatic coating and drying process: the moving speed of the second semi-finished product is preferably 150 to 200 m / min.
[0088] In the present invention, the hardened embossed layer and the antistatic release layer are preferably completed in a dual-function coating device, and the dual-function coating device preferably includes two processes of UV curing and drying curing. The antistatic layer is preferably completed in another coating device.
[0089] In a specific embodiment of the present invention, the prepared surface hardening coating and antistatic release coating are placed in the baths of their respective coating devices, wherein the bath of the surface hardening coating needs to be kept at a constant temperature of 50-60°C during coating, and the UV light dose is controlled at 600-800mj / cm 2The power of the UV lamp is 160W / cm. According to the coating speed and the total irradiation power, the temperature of the heat curing oven is set to 130-160℃. The temperature is distributed in the above curve, with the highest value in the middle of the oven. The coating speed is determined by the UV light dose and the length of the heat curing oven. However, because the two processes are connected in series, the speeds of the two processes must be coordinated. The correct situation is that the appearance of the film is not affected by the excessively high temperature of the oven (or the residence time is too long). These appearances are mainly caused by the deformation caused by the stretching of the film. In the heat curing process, under the same temperature conditions, the anti-static The amount of platinum added to the ionization coating is also an important factor affecting the speed. When the platinum concentration of the antistatic release coating is 50ppm to 80ppm, the thermal curing temperature of the antistatic release coating is 160℃ at the highest point, and the thermal curing residence time is 8 to 10 seconds. Because platinum (in the form of chelate) is easily contaminated by nitrogen, phosphorus, tin, sulfur compounds and their ions, these substances should be excluded from the entire coating process during the coating process, otherwise the residual adhesion rate will be reduced in the lightest case, and the antistatic release layer will be rubbed off and the process will fail in the most serious case. The film that has been coated with the antistatic release coating and thermally cured is cooled and ironed. The water temperature of the cooling wheel should be ≤35℃ when it is rolled up to the temperature of the second semi-finished product. If necessary, ice water is used to pass through the cooling wheel, and the ironed and cooled film (antistatic release coating) is rolled up to be coated with the back antistatic coating for use.
[0090] The preparation method provided by the invention has a simple production process, strong processability and easy material selection.
[0091] The present invention provides the application of the surface hardened embossed double-sided antistatic release film described in the above technical solution or the surface hardened embossed double-sided antistatic release film prepared by the preparation method described in the above technical solution in semiconductors, car color change films, electronics, displays or touch screens. In the present invention, the touch screen is preferably a mobile phone touch screen or a tablet computer touch screen.
[0092] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0093] The following examples are based on Figure 3 The embossed double-sided antistatic release film with a hardened coating is prepared according to the preparation flow chart. Figure 2 It is a schematic structural diagram of an embossed double-sided antistatic release film with a hardened coating prepared in an embodiment of the present invention.
[0094] Example 1
[0095] 1. The base material is Lucky Film (FP613) 50μ×1040mm;
[0096] 2. Install the embossed (concave) roller on the two-roller coating device. The embossed concave depth is 0.015mm and the line spacing is 0.6mm. If the depth is too deep, the lines will be deformed or easily cracked after coating, affecting the appearance and being unfavorable to the exhaust effect of downstream products.
[0097] 3. The coating machine uses a coating head with UV curing and a two-roller gravure coating head combination, and the light dose of UV light curing is set to 600±50mj / cm 2 The power meets the coating speed in this light dose range of 50-100m / min. The recommended lamp is 160W / cm. Too slow speed will reduce the clarity of the lines, and too high speed will cause paint splashing. The coating head is installed in an environment with a relative humidity of ≤50% and a temperature of 25±5℃.
[0098] 4. Before entering UV coating and applying antistatic release coating, the front side of the film (and the embossed hardened layer after curing) must be treated by a corona machine. The power of the corona machine should meet the surface energy of the front side of the film within the speed range of 54-56 dahns, and pre-drying should be carried out before UV curing;
[0099] 5. Preparation of surface hardening coating: A. Weigh siloxane-modified polyurethane acrylic monomer: acrylate monomer (trimethylolpropane triacrylate): nano-silica (particle size ≤ 30nm): leveling agent: photoinitiator and toluene in the proportion (mass) of 40:20:3:3:3:30, put the toluene solvent in a clean stainless steel container, turn on the mixer and put the siloxane-modified polyurethane acrylic monomer and acrylate monomer on the stirring container respectively and stir for 30 minutes (it is recommended to use an ultrasonic oscillator for better dispersion). B. After the solution is evenly dissolved, put the nano-silica, leveling agent and photoinitiator on the stirred solution and continue stirring for 10 minutes, then seal the upper part of the container with a brown film for standby use. The viscosity of the obtained surface hardening coating is 100-400mPa·s.
[0100] 6. Dilute 100 parts by mass of organopolysiloxane, 0.06 parts by mass of poly(3,4-ethylenedioxythiophene), 0.5 parts by mass of Dow Corning 297, 2.4 parts by mass of polyhydrogensiloxane (Bluestar 96A) and a platinum chelate catalyst in n-hexane to obtain an antistatic release coating, wherein the concentration of the platinum chelate catalyst in the antistatic release coating is 50 ppm; the solid content of the antistatic release coating is 4%, and the viscosity of the antistatic release coating is 10 to 40 mPa·s.
[0101] 7. Install a 100-mesh anilox roller on the two-roller coating head to coat the antistatic release layer; the anilox roller uses a ceramic roller (aluminum oxide) to reduce the impact of the roller surface roughness on the appearance of the film, which is mainly reflected in scratches on the film;
[0102] 8. Place the prepared surface hardening coating liquid in a bath at a constant temperature of 50-60°C;
[0103] 9. Put the prepared antistatic release layer coating liquid on the two-roll coating device;
[0104] 10. Start the coating equipment, raise the temperature of the pre-oven to 110 / 120℃ (2-section oven), and the main oven to 130 / 140 / 160 / 160 / 160 / 160 / 150 / 140 (8-section oven);
[0105] 11. After the oven temperature is reached, turn on the UV device and corona device, turn on the coater and slowly increase it to the rated speed (50-100m / min) for coating. Here, the relative humidity of the surface hardening coating environment is ≤50%; the temperature is 25±5℃, and the bath temperature is 50-60℃. High temperature will reduce the viscosity of the hardening coating liquid, and vice versa. This feature can be used to fine-tune the coating amount;
[0106] 12. The film after heat curing enters the cooling section for cooling. The temperature of the cooling section meets the temperature of the rolled product (semi-finished product) ≤ 35°C. The tension of the roll is reduced by 10-30%. The tension setting is adjusted according to the thickness of the film. In this case, it is 200N.
[0107] 13. Take the coated embossed antistatic release film (single-sided antistatic) to another coating machine for coating the back with antistatic coating. Before coating the back with antistatic coating, first perform corona treatment on the back of the film. The power of the corona machine should meet the requirement of achieving a surface energy of 54 to 56 dahns on the back of the film within the speed range. The mass percentage of poly(3,4-ethylenedioxythiophene) in the antistatic coating is 0.2%, and the solvent is a mixture of deionized water and isopropyl alcohol, wherein the mass ratio of deionized water to isopropyl alcohol is 1:3. The oven temperature is 110°C, and the machine speed is 200m / min (oven length is 28m, temperature is 90 / 100 / 110 / 110 / 110 / 100 / 95°C) to complete the double-sided antistatic function, i.e., complete the entire process;
[0108] After the product is produced according to the above Example 1, its main properties are shown in Table 1. Figure 1 This is an enlarged view of the structure of the embossed double-sided antistatic release film with a hardened coating prepared in Example 1 of the present invention.
[0109] Example 2
[0110] The preparation method is basically the same as that of Example 1, except that:
[0111] 1. The embossed (concave) roller with hardened coating in Example 2 has a concave depth of 0.02 mm and a line width of 0.6 mm;
[0112] 2. The ratio of the surface hardening coating in Example 2 is: siloxane-modified polyurethane acrylic monomer: acrylate monomer (trimethylolpropane triacrylate): nano-silicon dioxide (particle size ≤ 30 nm): leveling agent: photoinitiator and toluene in a ratio (mass) of 35:25:4:3:3:30;
[0113] 3. The light dose of UV curing in Example 2 is set to 700±50mj / cm 2 ;
[0114] 4. 100 parts by mass of the organopolysiloxane in Example 2, 0.1 parts by mass of poly(3,4-ethylenedioxythiophene), 0.5 parts by mass of Dow Corning 297, 2.4 parts by mass of polyhydrogensiloxane (Bluestar 96A) and a platinum chelate catalyst are diluted in n-hexane to obtain an antistatic release coating, wherein the concentration of the platinum chelate catalyst in the antistatic release coating is 65 ppm; the solid content of the antistatic release coating is 4%, and the viscosity of the antistatic release coating is 10 to 40 mPa·s.
[0115] Example 3
[0116] The preparation method is basically the same as that of Example 1, except that:
[0117] 1. 100 parts by mass of the organopolysiloxane, 0.5 parts by mass of poly(3,4-ethylenedioxythiophene), 0.5 parts by mass of Dow Corning 297, 2.4 parts by mass of polyhydrogensiloxane (Bluestar 96A) and a platinum chelate catalyst in Example 3 are diluted in n-hexane to obtain an antistatic release coating, wherein the concentration of the platinum chelate catalyst in the antistatic release coating is 65 ppm; the solid content of the antistatic release coating is 4%, and the viscosity of the antistatic release coating is 10 to 40 mPa·s;
[0118] 2. Adjust the UV light dose to 500mj / cm 2 ;
[0119] The performance test results of the embossed double-sided antistatic release film with hardened coating prepared in Examples 1 to 3 are shown in Table 1. From the results in Table 1, it can be seen that, from Examples 1 to 3, as the mass fraction of poly(3,4-ethylenedioxythiophene) in the antistatic release coating increases, the surface impedance of the surface hardened embossed double-sided antistatic release film prepared in Examples 1 to 3 decreases, the conductive efficiency increases, the single residual adhesion rate decreases significantly, and there is silicon migration. Compared with Example 1 and Example 2, the decrease in the quality of the photoinitiator in Example 1 will lead to a more obvious surface hardness of the film. Therefore, when producing the embossed double-sided antistatic release film with hardened coating, pay attention to the maintenance of the UV lamp, and pay attention to the change of UV dosage in the process will cause the product hardness to be insufficient.
[0120] Table 1 Comparison of physical and chemical properties of products in Examples 1 to 3
[0121]
[0122]
[0123] Note: 1. The test samples are placed in the experiment 24 hours after being removed from the machine, and the samples are cut according to national or industry standards;
[0124] 2. Results 1, 2 and 3 in Table 1 are the results of the products prepared in Example 1, Example 2 and Example 3, respectively, and Result 4 is the test result of a conventional embossed antistatic release film (a release film embossed with PE embossed film).
[0125] 3. The substrates of the three samples of results 1, 2 and 3 in Table 1 all use 50 μm PET film;
[0126] 4. The residual adhesion rate uses the tesa 7475 standard tape;
[0127] 5. The release force test uses chem-instrument AR-1000 instrument;
[0128] 6. Silicon migration was performed using Oxford's X-3500 X-ray fluorescence spectrometer;
[0129] 7. The surface impedance test uses ACL Staticide's 800 surface impedance meter;
[0130] 8. The line depth test uses Taylor Hobson's S116 surface roughness tester;
[0131] From the above embodiments, it can be seen that the embossed double-sided antistatic release film with a hardened coating provided by the present invention has excellent temperature resistance, high residual adhesion rate, low silicon migration, small depth change rate of the grain line and double-sided antistatic function. Its high temperature resistance will have a positive effect on downstream applications in coating high-performance industrial tapes. Its high temperature resistance can help the tape production industry save catalysts under the same production conditions, because the cross-linking temperature of the tape is a very important factor. High-temperature cross-linking will save the addition of catalysts for the adhesive tape, and can obtain high peeling force and long-term weather resistance.
[0132] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A surface hardened embossed double-sided antistatic release film, characterized in that: It comprises a polyethylene terephthalate film, a hardened embossed layer arranged on the front side of the polyethylene terephthalate film, an antistatic release layer arranged on the surface of the hardened embossed layer, and an antistatic layer arranged on the back side of the polyethylene terephthalate film; The hardened embossed layer is obtained by photocuring a surface hardening coating, wherein the surface hardening coating comprises a siloxane-modified polyurethane acrylic monomer, an acrylate monomer, a first organic solvent, a flattening agent and a photoinitiator; The antistatic release layer is formed of an antistatic release coating, and the antistatic release coating includes a conductive polymer resin, an anchoring agent, an organic polysiloxane, a polyhydrogen siloxane, a platinum chelate catalyst, and a second organic solvent.
2. The surface-hardened embossed double-sided antistatic release film according to claim 1, characterized in that: The acrylate monomer is trimethylolpropane triacrylate, and the first organic solvent is toluene; The mass ratio of the siloxane-modified polyurethane acrylic monomer to the acrylate monomer is (35-40): (20-25); The mass ratio of the siloxane-modified polyurethane acrylic monomer to the leveling agent is (35-40): (3-5); The mass ratio of the siloxane-modified polyurethane acrylic monomer to the photoinitiator is (35-40):3; The viscosity of the surface hardening coating is 100-400 mPa·s.
3. The surface-hardened embossed double-sided antistatic release film according to claim 1, characterized in that: The surface hardening coating also includes nano silicon dioxide; the particle size of the nano silicon dioxide is less than or equal to 30 nm; the mass ratio of the siloxane-modified polyurethane acrylic monomer to the nano silicon dioxide is (35-40): (3-5).
4. The surface-hardened embossed double-sided antistatic release film according to any one of claims 1 to 3, characterized in that: The embossing depth of the hardened embossed layer is 10 to 30 μm, and the width of the embossing line interval is 0.5 to 2 mm.
5. The surface-hardened embossed double-sided antistatic release film according to claim 1, characterized in that: The conductive polymer resin includes one or more of polythiophene, polythiophene derivatives and polyanionic polymers, the polyanionic polymer includes polymeric hydroxy acid and / or polymeric sulfonic acid; the polymeric hydroxy acid includes one or more of polyacrylic acid, polymethacrylic acid and polymaleic acid, and the polymeric sulfonic acid includes polystyrene sulfonic acid; The second organic solvent is n-hexane.
6. The surface-hardened embossed double-sided antistatic release film according to claim 1 or 5, characterized in that: The conductive polymer resin is polythiophene and / or a polythiophene derivative, and the mass ratio of the organopolysiloxane to the polythiophene and / or the polythiophene derivative is 100:(0.05-0.5); The mass ratio of the organopolysiloxane to the anchoring agent is 100:(0.5-1); The mass ratio of the organopolysiloxane to the polyhydrogensiloxane is 100:(1.5-3); The mass concentration of the platinum chelate catalyst in the antistatic release coating is 50 to 80 ppm; The solid content of the antistatic release coating is 1.5-5%; The viscosity of the antistatic release coating is 10-40 mPa·s.
7. The surface-hardened embossed double-sided antistatic release film according to claim 1, characterized in that: The antistatic layer is formed by an antistatic coating, which includes an antistatic substance and a third solvent. The antistatic substance is polythiophene and / or a polythiophene derivative. The mass percentage of the antistatic substance in the antistatic coating is 0.05-0.5%. The third solvent is water or isopropanol, or a mixture of water and isopropanol.
8. The method for preparing the surface-hardened embossed double-sided antistatic release film according to any one of claims 1 to 7, characterized in that: The following steps are involved: Using an embossing roller to apply a surface hardening coating on the front side of the polyethylene terephthalate film to obtain a surface hardened wet film, and then sequentially pre-drying and light-curing the surface hardened wet film to obtain a hardened embossed layer to obtain a first semi-finished product; Using an anilox roller to apply an antistatic release coating on the surface of the hardened embossed layer of the first semi-finished product to obtain an antistatic release wet film, and then subjecting the antistatic release wet film to thermal curing to obtain an antistatic release layer to obtain a second semi-finished product; The back side of the polyethylene terephthalate film of the second semi-finished product is coated with an antistatic coating to obtain an antistatic wet film, and then the antistatic wet film is dried to obtain the antistatic layer, thereby obtaining the surface-hardened embossed double-sided antistatic release film.
9. The preparation method according to claim 8, characterized in that: The embossing depth of the embossing roller is 0.01-0.03 mm, the width of the embossing line interval is 0.5-2 mm, the humidity of the coating environment is ≤50%, the temperature is 25±5° C., the moving speed of the polyethylene terephthalate film is 50-100 m / min, the temperature of the surface hardening coating is 50-60° C., the pre-drying temperature is 110-130° C., the light curing is carried out under the condition of ultraviolet light irradiation, the wavelength of the ultraviolet light is 200-400 nm, and the dose of the ultraviolet light is 600-800 mj / cm 2 , power is 100~160W / cm; The mesh number of the anilox roller is 80 to 200 meshes, and the coating wet weight of the antistatic release coating is 4 to 10 g / m 2 , the thermal curing temperature is 130-160°C, and the time is 8-10s; The antistatic coating is coated by two gravure rollers, the mesh number of the gravure of the two gravure rollers is 300-350 meshes, and the coating wet weight of the antistatic coating is 3-5 g / m 2 The antistatic coating has a dry coating weight of 0.5 to 1.5 g / m 2 .
10. The surface-hardened embossed double-sided antistatic release film described in any one of claims 1 to 7 or the surface-hardened embossed double-sided antistatic release film prepared by the preparation method described in claim 8 or 9 is not limited to the application in semiconductors, car color change films, electronics, displays or touch screens.
